1998
DOI: 10.1007/978-94-011-4820-7_6
|View full text |Cite
|
Sign up to set email alerts
|

Element Settling in the Solar Interior

Abstract: Abstract.Element settling inside the Sun now becomes detectable from the comparison of the observed oscillation modes with the results of the theoretical models. This settling is due, not only to gravitation, but also to thermal di usion and radiative acceleration (although this last e ect is small compared to the two others ). It leads to abundance variations of helium and heavy elements of = 10% below the convective zone. Although not observable from spectroscopy, such v ariations lead to non-negligible modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…These effects were investigated by e.g. Turcotte et al (1998), Vauclair (1998), Turcotte & Wimmer-Schweingruber, (2002) and Yang (2016Yang ( , 2019. Yang (2019) took the effects of rotation on mixing into account (see below).…”
Section: Solar Abundances Of the Elements Photosphere Sunspots Corona...mentioning
confidence: 99%
“…These effects were investigated by e.g. Turcotte et al (1998), Vauclair (1998), Turcotte & Wimmer-Schweingruber, (2002) and Yang (2016Yang ( , 2019. Yang (2019) took the effects of rotation on mixing into account (see below).…”
Section: Solar Abundances Of the Elements Photosphere Sunspots Corona...mentioning
confidence: 99%
“…Comparisons between models and helioseismic inversions have been made by, e.g., ChristensenDalsgaard et al (1996), Richard and Vauclair (1997), Turck-Chie`ze et al (2001a) or Couvidat et al (2003). Already early helioseismic results showed that the sound speed between 0.3 and 0.7 R x (below the convection zone) was higher than predicted by models, such that the assumed opacity in the models had to be re-assessed, as well as element settling and small mixing near that area (Brun et al, 1998(Brun et al, , 1999Vauclair, 1998;Turck-Chie`ze et al, 1998). A comparison of modelled and measured sound speed in the solar interior is shown in Figure 6.…”
Section: The Solar Interiormentioning
confidence: 92%